2006
DOI: 10.1007/bf02893446
|View full text |Cite
|
Sign up to set email alerts
|

Leptin — From regulation of fat metabolism to stimulation of breast cancer growth

Abstract: Leptin restricts intake of calories as a satiety hormone. It probably stimulates neoplastic proliferation in breast cancer, too. Growth of malignant cells could be regulated by various leptin-induced second messengers like STAT3 (signal transducers and activators of transcription 3), AP-1 (transcription activator protein 1), MAPK (mitogen-activated protein kinase) and ERKs (extracellular signal-regulated kinases). They seem to be involved in aromatase expression, generation of estrogens and activation of estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Growth of breast cancer cells could be regulated by various leptin-induced secondary messengers like STAT3, activator protein (AP-1), mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinases (ERK), involved in aromatase expression, generation of estrogens, and activation of estrogen receptor-a in malignant breast epithelium (31). Higher circulating levels of leptin found in obese subjects could be a growthenhancing factor (as supported by in vitro studies), whereas lower levels of adiponectin found in obese women may allow growth-promoting effects of leptin (31). Fish oil rich in w-3 PUFA has been shown to increase plasma levels of adiponectin in rodents and in human subjects and to decrease plasma leptin concentrations (26).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of breast cancer cells could be regulated by various leptin-induced secondary messengers like STAT3, activator protein (AP-1), mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinases (ERK), involved in aromatase expression, generation of estrogens, and activation of estrogen receptor-a in malignant breast epithelium (31). Higher circulating levels of leptin found in obese subjects could be a growthenhancing factor (as supported by in vitro studies), whereas lower levels of adiponectin found in obese women may allow growth-promoting effects of leptin (31). Fish oil rich in w-3 PUFA has been shown to increase plasma levels of adiponectin in rodents and in human subjects and to decrease plasma leptin concentrations (26).…”
Section: Discussionmentioning
confidence: 99%
“…Serum leptin level also increases in patients with some cancer types [76,80] . Leptin is considered an agent responsible for overcoming the antiproliferative effect of antiestrogen therapy in different cancer types.…”
Section: Leptin Jak-stat Signalingmentioning
confidence: 97%
“…Leptin receptor is homologous to gp130 and can activate JAK2, mainly STAT3, but also STAT5, STAT6, STAT1 proteins [74][75][76][77] . SOCS3 is a negative regulator of leptin JAK-STAT signaling [18,78,79] .…”
Section: Leptin Jak-stat Signalingmentioning
confidence: 99%
“…Although first discovered in 1994 (121), its role in cancer etiology is only recently appreciated. Adipose tissue is quantitatively the most important source of leptin and the primary determinant of circulating leptin levels (122)(123)(124). Leptin is widely known for its ability to counteract obesity by inducing satiety and limiting caloric intake (123), but paradoxically, human obesity is associated with higher levels of circulating leptin, possibly signifying leptin resistance (57,122).…”
Section: Insulin Resistancementioning
confidence: 99%
“…CRP is a hepatocyte-derived, acute phase protein considered to be the prototypical marker of inflammation in humans (174) and might also affect postmenopausal breast cancer risk. CRP levels correlate positively with weight (175,176) and weight gain (177) and have been Weight loss decreases body fat, which is the main source of circulating leptin (122)(123)(124). Although leptin can improve insulin sensitivity (145), elevated leptin levels are associated with insulin resistance (117).…”
Section: Physical Activity and Postmenopausal Breast Cancer Cancer Epmentioning
confidence: 99%